Increasing eutrophication driven by the increase of phosphate discharge in a subtropical bay in the past 30 years - He, Guirong; Lao, Qibin; Jin, Guangzhe; Zhu, Qingmei; Chen, Fajin (Frontiers in Marine Science, 2023)
Although great efforts have been made to decrease nutrient (notably nitrogen and phosphorus) loads and lighten related environmental damages, coastal eutrophication remains a persistent environmental crisis. To estimate whether the rapid development of the local economy has accelerated the eutrophication in Zhanjiang Bay, a newly developing industry in South China, the combination of the seasonal nutrients and other physicochemical parameters from twenty cruises during 2017-2021 and historical data (past 30 years) was analyzed in this study. The results showed that the eutrophication in the upper bay is significantly higher than that in the lower bay (more than 8 times), which is mainly related to the terrestrial input and weak hydrological conditions in the upper bay. Also, eutrophication is more severe in the rainy seasons than that in the dry seasons (nearly 2 times) because abundant nitrogen and phosphorus were brought into the bay by terrestrial discharge and river water. From a long-term perspective, dissolved inorganic nitrogen concentrations have been effectively controlled in Zhanjiang Bay, while phosphate concentration increased sharply in the past 30 years. Correspondingly, the eutrophication in Zhanjiang Bay significantly increased over the past 30 years, and the eutrophication index in the recent 5 years (2017-2021) is nearly 10 times that of the 1990s, suggesting that the increase of phosphate discharge from the increasing industrial factories around Zhanjiang Bay, rather than nitrogen discharge is the culprit causing the aggravation of eutrophication. Our study is essential to effectively implement a land-ocean integrated nitrogen and phosphorus control strategy to improve water quality and mitigate eutrophication in the bay.